2021
DOI: 10.3390/ijms222212209
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Flavonoid Apigenin on Male Reproductive Health: Inhibition of Spermatogonial Proliferation through Downregulation of Prmt7/Akt3 Pathway

Abstract: Apigenin, a common dietary flavonoid abundantly present in a variety of fruits and vegetables, has promising anticancer properties. As an effector of apigenin in myoblasts, protein arginine methyltransferase 7 (Prmt7) is required for male germ cell development. However, whether apigenin may influence male reproductive health through Prmt7 is still unclear. To this end, mouse spermatogonia were treated with different concentrations (2.5 to 50 μM) of apigenin for 48 h, which showed that apigenin could cause redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Our previous work identified that Prmt7 regulated the proliferation of GC-1 cells (a type of mouse spermatogonial cell line) as the Prmt7 knockdown reduced their proliferation [ 5 ]. However, the underlying molecular mechanisms are still unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work identified that Prmt7 regulated the proliferation of GC-1 cells (a type of mouse spermatogonial cell line) as the Prmt7 knockdown reduced their proliferation [ 5 ]. However, the underlying molecular mechanisms are still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Prmt7 deficiency can lead to the defective proliferation of mouse primordial germ cells during the embryonic stage [ 7 ]. Prmt7 downregulation reduced GC-1 mouse spermatogonial proliferation [ 5 ]. Prmt7 overexpression promotes the malignant progression of nonsmall cell lung cancer cells [ 42 ] and the growth of renal cell carcinoma [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apigenin, also known as 4,5,7-trihydroxy flavone, is a potential therapeutic agent with antioxidant, anti-inflammatory, antibacterial, and antiviral properties that has been investigated in the treatment of cancer due to its high anti-tumoral activity. [36][37][38][39] By inhibiting the aromatase enzyme, apigenin can cause changes in semen parameters, androgen levels, and the hypothalamo-pituitarygonadal axis in the male reproductive system. Therefore, it can be used as a therapeutic agent in male infertility alone or in combination therapy.…”
Section: Apigeninmentioning
confidence: 99%
“…However, it is important to note that the concentration of apigenin used can have different effects. A study on mouse sperm production revealed that certain doses of apigenin interfered with the growth of sperm cells, which could lead to lower sperm count and higher abnormal sperm count 19 .…”
Section: Introductionmentioning
confidence: 99%